2008
DOI: 10.1889/1.3069660
|View full text |Cite
|
Sign up to set email alerts
|

24.2: Single Layer Al‐Ni‐La‐Si Interconnections for Source and Drain of LTPS‐TFT LCDs Using Direct Contacts with both ITO and poly‐Si

Abstract: It was demonstrated for the first time that the use of Al‐Ni‐La‐Si alloy films for the direct contacts of interconnection lines with both ITO and poly‐Si was feasible for the LTPS‐TFTs. Measured contact resistivity was in the order of 10−4 Ω.cm2 for ITO and Al‐0.6 at.% Ni‐0.1 at.% La‐0.5 at.% Si. The Al alloy films patterned on poly‐Si were found to be stable below 350 °C. It was also found that Al alloy has good dry etching characteristics such as a high etching rate and good selectivity to photo‐resist, suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…1(b) shows the S/D and gate interconnections using direct contacts. [15][16][17] Compared with the conventional structure in Fig. 1(a), the TFT structure in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1(b) shows the S/D and gate interconnections using direct contacts. [15][16][17] Compared with the conventional structure in Fig. 1(a), the TFT structure in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we experimentally demonstrated that Al-Ni alloys possess characteristics most suitable for direct contacts. 16,17) Indeed, the developed Al-Ni alloy interconnections have already been used for the massproduction of LCD panels to reduce manufacturing cost. Although we found that Al-Ni alloys are practically usable, it has not yet been understood why the direct contact between ITO and Al-Ni alloy films exhibits good electrical conduction and what is the major current path across the contact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 To answer these questions, we investigated the current path using nanoprobes 13,14 and evaluated the band diagram of the ITO/Al-Ni alloy contact by X-ray photoelectron spectroscopy ͑XPS͒ and ultraviolet photoelectron spectroscopy ͑UPS͒. 15-18 As a result, we learned how to achieve even lower resistivity of the ITO/ Al-Ni alloy contact compatible with the production process of a-Si TFTs.…”
mentioning
confidence: 99%
“…1b, Al-Ni alloy interconnections were developed for the first time for direct contacts between the ITO film and the Al-Ni alloy interconnections. 11,12 Presently, the developed Al-Ni alloy interconnections are ready for use in mass production of LCD panels.…”
mentioning
confidence: 99%